Starategi Dalam Pengolahan Bahan Koleksi Anak di Taman Bacaan Kampung Nelayan Kota Medan - Yusniah Yusniah; Chintya Almira; Nazmiah Yusdi Arwana ; Novita Sari; Elsa Annisa Batu Bara (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
A community reading garden is a place dedicated to the community and is usually run by the community itself and the government. The presence of a community reading garden around the house is meant to spark an interest in reading. Taman Bacaan Masyarakat itself is a kind of public library. The existence of a community reading garden in the midst of the community is intended to increase public interest in reading in general and is used as an informal means of education. This study aims to apply the strategy of developing children's reading interest through the reading collection of Kampung Nelayan Reading Center. This research method uses qualitative research method based on the collected information. The results of this study indicate that the book collection of the floating library in the fishing village has a total of 400 books donated by the Padang city government and donors. The collection is a collection provided by the director of Kampung Nelayan Reading Center. Introducing children to a love of reading is not easy, especially when children don't learn to read from birth. Keywords: Children's Reading Collection Material, Community Reading Gardens